Pemikiran Ibn Khaldun dalam Manajemen Sumber Daya Manusia - Wiryanto, Wisber (Jurnal Manajemen (Edisi Elektronik), 2020)
Ibn Khaldun (732-808 H) was a figure of Muslim scholars in the classical era and an author of the Mukaddimah’s which contains both naqli and aqli knowledge. In assumption, the Mukaddimah contains human resource management (HRM) also. Therefore, a study was conducted with a problem formulation, how did Ibn Khaldun’s thought on HRM in the Mukaddimah’s? The objective of this research was to identify the concepts of Ibn Khaldun’s thought on HRM. This study was conducted using the library research method. The Mukaddimah as a source of data or subject; and the HRM’s as focus or object this study. After collecting data, analyzing data was carried out, using the descriptive qualitative technique. The study was conducted in the year 2020. The result of this study indicated an existence of Ibn Khaldun’s thoughts in good HRM which has relevance to HRM contemporary, namely the concept of employee typology and ethics officials. This concept was evidenced by the contribution of Ibn Khaldun’s thought on HRM science sourced from the al-Quran, hadith, and Islamic legacy. Therefore, this study suggests awarding Ibn Khaldun as the founding father of human resource management.